Cellular therapy for acute myeloid Leukemia – Current status and future prospects. (September 2019) - Hansrivijit, Panupong; Gale, Robert Peter; Barrett, John; Ciurea, Stefan O.
Abstract: Acute myeloid leukemia (AML) is a disease most commonly affecting older individuals with a high mortality. Despite the recent introduction of many novel agents, only a few were shown to significantly impact the outcome of this disease. Recent advances using chimeric antigen receptor (CAR) T-cells for B-cell acute lymphoblastic leukemia and non-Hodgkin's lymphoma have generated a tremendous interest for this strategy. Moreover, early results using high-dose natural killer (NK) cell therapy show promise for the treatment of patients with advanced AML. Other cell products like cytokine-induced killers (CIK) or CAR T-cells targeting CD33 or CD123 surface antigens are being developed. NK-cells expressing a CAR against myeloid antigens may combine the benefits of targeting AML cells with NK cell mediated killing. It is unknown whether such approaches targeting AML will spare normal hematopoiesis or would need to be used in combination with hematopoietic stem cell transplantation. Here we review the current state of cell therapy for patients with AML and consider future prospects.